2018
DOI: 10.3889/oamjms.2018.076
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Assessment of the Proliferation Capacity of Gingival and Periodontal Ligament Stem Cells from Diabetic Patients

Abstract: BACKGROUND:Stem cells have recently received great interest as potential therapeutics alternative for a variety of diseases. The oral and maxillofacial region, in particular, encompasses a variety of distinctive mesenchymal (MSC) populations and is characterized by a potent multilineage differentiation capacity.AIM:In this report, we aimed to investigate the effect of diabetes on the proliferation potential of stem cells isolated from controlled diabetic patients (type 2) and healthy individuals.SUBJECTS & MET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…MSC auto-transplantation protocols could be used to dramatically improve the outcomes of serious bony defects and non-unions. However, the limiting factor of any such treatment option is the time needed to expand an individual’s extracted stem-cell population [7]. Human bone marrow mesenchymal stem cells (hBM-MSCs) can be cultured using a variety of different techniques and methodologies, including traditional monolayer culture, biomatrix embedding of cells, and as of recently, self-assembled spheroid culture [8].…”
Section: Introductionmentioning
confidence: 99%
“…MSC auto-transplantation protocols could be used to dramatically improve the outcomes of serious bony defects and non-unions. However, the limiting factor of any such treatment option is the time needed to expand an individual’s extracted stem-cell population [7]. Human bone marrow mesenchymal stem cells (hBM-MSCs) can be cultured using a variety of different techniques and methodologies, including traditional monolayer culture, biomatrix embedding of cells, and as of recently, self-assembled spheroid culture [8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PDL-MSCs had more proliferative potentials compared to G-MSCs in both healthy and diabetic conditions. All isolated cell populations showed positive expression of CD90 and CD105 and negative expression of CD45 without details of significant difference between diabetic and non diabetic cells [ 146 ]. Another study compared PDL-MSCs from teeth with periodontitis from diabetic patients to those extracted from non-diabetics both sound and with periodontitis.…”
Section: Tissue Engineering and Periodontal Regenerationmentioning
confidence: 99%
“…The physical condition of donors is a key factor to properties of GMSCs. Assem et al revealed that GMSCs exhibited a greater proliferation rate and higher surviving in normal individuals than the diabetic patients [67]. Moreover, GMSCs exosome from diabetic mice showed reduced IL-1RA and decreased Fas expression when compared to WT GMSCs [40].…”
Section: Analysis Of Factors Influencing the Function Of Gmscmentioning
confidence: 99%